2006
DOI: 10.1161/circulationaha.105.537712
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Acute Coronary Syndrome Show Oligoclonal T-Cell Recruitment Within Unstable Plaque

Abstract: Background-Recent studies indicate that T-cell activation may play an important role in the pathophysiology of acute coronary syndromes (ACS). However, although those studies detected T-cell expansion in peripheral blood cells, demonstration of specific T-cell expansion within the plaque of patients with ACS is lacking. The present study aims to address whether a specific, immune-driven T-lymphocyte recruitment occurs within the unstable plaque of patients with ACS. Methods and Results-We simultaneously examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 34 publications
(52 reference statements)
3
79
0
4
Order By: Relevance
“…We verified whether these events could be identified at the molecular levels in the plaque, in which oligoclonal T cell response has recently been documented (35). First, a difference in LC germline sequences frequency was observed in the two populations, with only 2 LC germline sequences in CPS, compared with 55 LC GLS in PBLs ( p ϭ 0.014).…”
Section: Ag-driven Evolution Of B Cells In Coronary Plaquessupporting
confidence: 54%
“…We verified whether these events could be identified at the molecular levels in the plaque, in which oligoclonal T cell response has recently been documented (35). First, a difference in LC germline sequences frequency was observed in the two populations, with only 2 LC germline sequences in CPS, compared with 55 LC GLS in PBLs ( p ϭ 0.014).…”
Section: Ag-driven Evolution Of B Cells In Coronary Plaquessupporting
confidence: 54%
“…Reaction mixtures conplaque rupture 5,6) . Unstable plaques are characterized by the activation and infiltration of circulating effector T cells with specificity for both autologous and external antigens 7,8) .…”
Section: Quantification Of Sj-trec By Real-time Pcrmentioning
confidence: 99%
“…Ten days after stimulation with phytohemagglutinin, IL-2, and feeder cells, the specificity of the T-cell cultures (plaque as well as peripheral blood derived) was analyzed by incubating 5ϫ10 4 T cells and 5ϫ10 4 autologous, irradiated PBMCs as APCs for 4 days in T-cell medium either with or without influenza virus (10 tissue culture infectious dose [TCID 50 ] per cell) in 96-well, round-bottom culture plates (Costar). All combinations were analyzed in quadruplicate.…”
Section: T-cell Proliferation Assaysmentioning
confidence: 99%
“…1 In patients with unstable angina and acute myocardial infarction, the numbers of recently activated T cells are significantly increased. 2,3 Furthermore, de Palma et al 4 showed that unstable but not stable coronary atherosclerotic lesions contain oligoclonal populations of T lymphocytes, which shows that antigen-driven activation and proliferation of effector T cells typically occur in unstable plaques.…”
mentioning
confidence: 99%